Attitude and Awareness among UG, Intern & PG students about Management of Medical Emergencies in Dental Office: A Survey Study - S, Sunitha.; Inamdar, Harshada; Hamid, Nida; Srinivasan, Arun priya; Gulia, Sunil Kumar; Abraham, Abin Ann (International Journal of Psychosocial Rehabilitation, 2020)
Background: Medical emergencies can occur during dental practice which can even be life-threatening to a patient. Knowledge, awareness and training regarding medical emergencies are critical to the practice of dentistry.Aim: To assess the attitude and awareness among undergraduate (UG), intern & postgraduate (PG) dental students about management of medical emergencies in dental office.Materials & Methods: A questionnaire based survey was conducted to assess the attitude and awareness among UG, intern & PG dental students about management of medical emergencies in dental office. The questionnaire for the study consisted of eight closed- ended questions. Responses were recorded and descriptive analysis was used for statistical analysis of the data.Results: 80.30% of UG students, 88.68% interns and 95.24% of PG dental students enquire about the medical history of their patients. Only 43.94% of UG students, 56.60% interns and 66.67% of PG students claimed that they had attended any workshop on emergency training or management programs. 65.15% of UGs, 58.49% of interns and 45.24% of PGs, were not confident to handle any emergency condition at their dental clinic.Conclusion: UG, intern and PG dental students do not feel confident in handling medical emergencies.